A Javanese Response to Islamic Identity - Hendro Prasetyo (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
New Order government emphasized political stability for the sake of economic development. This is partly characterized by political expediency